An experimental investigation of a realistic-scale seasonal solar adsorption storage system for buildings. (October 2017) - Köll, R.; van Helden, W.; Engel, G.; Wagner, W.; Dang, B.; Jänchen, J.; Kerskes, H.; Badenhop, T.; Herzog, T.
Highlights: Seasonal closed sorption storage system demonstrated successfully in realistic- scale for the first time. Significant improvement of energy density due to the novel charge boost technique. Energy density of 178 kWh/m 3 could be proven experimentally under real condition. A solar fraction of 83% was achieved during automatic operation. Abstract: The mismatch between the abundant available solar energy in summer and the heat demand in winter can be overcome by compact seasonal thermal energy storages, which are characterized by low thermal losses and avanvanvan high energy density. A promising technology to meet these special requirements is through closed sorption storage. Within this paper a demonstration system for domestic hot water and space heating for a single family house was designed and demonstrated. The working pair binderfree zeolite 13X and water vapor was chosen for this purpose. Since the novel charge boost mode was applied, an energy density of 178 kWh/m 3 has been achieved, which is almost 3 times higher compared to the conventional sensible water storage energy density. The demonstration system was tested successfully during the heating period 2015/16 in full automatic operation. A solar fraction of 83.5% for covering the space heating and domestic hot water demand was reached during this period.